Elucidating the degradation reaction pathways for the hydrothermal carbonisation of hemp via biochemical compositional analysis. (15th June 2021) - Keiller, Benjamin G.; Potter, Matthew; Burton, Rachel A.; van Eyk, Philip J.
Highlights: Hemicellulose is rapidly degraded under hydrothermal conditions. Cellulose was highly resistant at 200 °C and 230 °C, but decomposes more rapidly at 260 °C. Lignin degradation is comparatively complex, with a portion of the lignin being inert under the conditions tested. Abstract: Hydrothermal carbonisation (HTC) is a technology used to convert biomass and other feedstocks into a high-energy "hydrochar" with numerous potential applications in solid fuels, activated carbons, and carbon sequestration, among others. The conversion of lignocellulosic biomasses involves a complex, interconnected set of reactions that result in the breakdown of hemicellulose, cellulose and lignin, the precise mechanisms and kinetics of which are at present poorly understood. Hemp stem and seed hulls are subjected to HTC at three temperatures (200 °C, 230 °C, 260 °C), and four residence times (0, 15, 30, 60 min), and the hydrochars produced were analysed for hemicellulose, cellulose and lignin content. The degradation for each macromolecule was characterised using Arrhenius kinetics, and it was found that hemicellulose degraded rapidly with a 1.3rd order reaction, while cellulose degraded more slowly. A portion of lignin in each hemp tissue was found to be inert under HTC conditions; hull lignin degraded rapidly to a constant level of 31% in a first order reaction, while two models were built describing stem lignin, one with an assumed inert portion of 34%, and another with an assumed inert portion of 21%.